Respecifying Mediated Interaction. Issue 4 (1st October 2016) - Arminen, Ilkka; Licoppe, Christian; Spagnolli, Anna
ABSTRACT: In this introduction to the special issue on "Orders of Interaction in Mediated Settings, " we explore the fundamentals of an ethnomethodological/conversation analytical perspective on mediated social interaction. We take an exchange to qualify as "mediated" when the people involved orient to the affordances that the mediating channel (phone, e-mail, videolink, and so on) offers. After specifying what we mean by this sense of mediation, and comparing it to others, we offer an overview of recent developments in the study of mediated practices. We argue that the trajectory is, and should be, away from the "deficiency" perspective previously common in the literature, and we suggest some guidelines to avoid commonsensical pitfalls in studying mediated settings.